Sex, age, and cohabitation status: is it associated with perceived need of follow-up after percutaneous coronary intervention?. (3rd October 2022) - Hjertvikrem, N; Instenes, I; Borregaard, B; Brors, G; Falun, N; Helmark, C; Palm, P; Pettersen, T R; Rotevatn, S; MacNeil Vroomen, J L; Zwisler, A D; Norekval, T M
Abstract: Background: Health status, and clinical- and sociodemographic factors influence the type of follow-up care for patients after percutaneous coronary intervention (PCI). However, patients' perceived need for follow-up and how this is associated with health status, sociodemographic and clinical variables in countries with different follow-up after PCI is scarcely examined. Norway and Denmark have similar healthcare systems, yet, only Danish patients are routinely referred to cardiac rehabilitation (CR). Aim: To determine how patients' perceived need for follow-up is associated with health status, and clinical and sociodemographic factors in two Nordic countries with different CR referral practices. Methods: Real-world data from 3417 patients at seven Norwegian and Danish university hospitals were collected in the prospective multicentre CONCARDPCI study. Patients' perceived need for follow-up were obtained two months post-discharge (index event). Sociodemographic characteristics were obtained by self-report during the index hospitalization. Clinical data were collected from patients' medical records and the Norwegian Registry on Invasive Cardiology. Mental and physical health were measured using the disease-specific Myocardial Infarction Dimensional Assessment Scale (MIDAS) and the generic RAND-12 questionnaire. We used t-tests and chi-square tests to test the differences between patients that want and do not want follow-up. Logistic regression further scrutinized the aims, reported as odds ratios (ORs) with 95% confidence intervals (CIs). Results: Most patients were men (78%) with a mean age of 66 years (SD 11). Those not wanting follow-up were older (mean 4.8 years, p<0.001), more often men (82% vs 78%, p=0.043), had lower education level (primary school 33% vs 16%, p<0.001), and had more often three or more comorbidities (54% vs 43%, p=0.003). They reported, however, to be healthier on both mental component scores (MIDAS emotional 16.4 vs 25.1, p<0.001, RAND-12 Mental 53.3 vs 48.4, p<0.001) and physical component scores (MIDAS Physical 19.8 vs 27.9, p<0.001, RAND-12 Physical 50.3 vs. 46.6, p<0.001). Stratified by country, for Norwegian patients, not wanting follow-up was almost twice as likely if living alone (OR 1.93, CI 1.22; 3.06), half as likely if being a woman (OR 0.48, CI 0.26; 0.85), increasingly likely with age (OR 1.06, CI 1.04; 1.08] and decreasingly likely with educational level (e.g. university >4 years: OR 0.30, CI 0.16; 0.55). In contrast, age, sex and cohabitation status was not significantly associated with perceived need of follow-up for Danish patients. Conclusions: Our findings suggest that sociodemographic factors are more important for patients' perceived need for follow-up than both health status and patient clinical characteristics. Country differences further suggest that there is not an easy way to classify patients' needs, and a one-size-fits-all follow-up programme may not exist in either CR pathways. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): The Western Norway Health Authority, The Norwegian Nurses Association